2006
DOI: 10.1021/ic051775h
|View full text |Cite
|
Sign up to set email alerts
|

Thioamide Pincer Ligands with Charge Versatility

Abstract: This paper reports the synthesis and characterization of three complexes, two palladium and one platinum, with 2,6-bis-thioamido-phenyl and 2,6-bis-thioamido-pyridine ligands. The ligands show internal charge versatility by losing protons from a phenyl CH (I) or from amide NH's (II and III). The complexes were also examined as Heck catalysts, and the palladacycle, I, was found to be more effective compared to the others. The crystal structures of the complexes are also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 28 publications
2
51
0
Order By: Relevance
“…However, the 1 H NMR and single-crystal X-ray analyses showed that only the S^C^S coordination mode occurred (Figure 4a). 39,40 Although the electronegativity of nitrogen is higher than that of sulfur, the metalS bonds are stabilized by backdonation from the metalH …”
Section: Ta Ligandsmentioning
confidence: 99%
“…However, the 1 H NMR and single-crystal X-ray analyses showed that only the S^C^S coordination mode occurred (Figure 4a). 39,40 Although the electronegativity of nitrogen is higher than that of sulfur, the metalS bonds are stabilized by backdonation from the metalH …”
Section: Ta Ligandsmentioning
confidence: 99%
“…The molar conductance of complexes (10 -3 M) were measured in DMF using Wiss-Werkstatter Weihem obb type LBR conductivity meter. The magnetic susceptibility was measured on a gouy balance using Hg[CO(SCN) 4 ] as calibrant.…”
Section: Preparation Of Ruthenium (Iii) Complexesmentioning
confidence: 99%
“…Bowman-James's group [4][5] and Kanbara and Co-worker [6][7][8] have reported that thioamide based Pincer complexes are photoluminescent and have catalytic activity. The group of Henderson [9][10][11] has reported the synthesis and structural characterization of various transition metal complexes containing chelating thioamide derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…havior was observed for Pd complexes of thioamidic SNS pincer ligands but protonation constants were not determined. [19] Unfortunately, although the protonation equilibria of several complexes were investigated in the last decade [16,17] the dissociation constants were all referenced to the HP(Cy) 3 + standard, and no direct comparison with those values is possible. Titration of HEtSNS by UV/Vis was not possible due to the absence of suitable variations in the absorption spectra.…”
Section: Acid-base Properties Of [Rh(co)(etsns)]mentioning
confidence: 99%